Building sustainable design performance through integrated value management practice - Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar; Ibrahim, Siti Halipah (Springer Singapore, 2015)
Maintenance management is a combination of all technical and administrative actions, including supervision actions, intended to retain an item in or restore it to a state in which it can perform a required function. Value management is a proactive, creative, problem-solving service, utilizing a multi-disciplinary team-oriented plan of attack to make explicit the client’s value system using functional analysis to discover the relationship between time, cost and quality with the aim of maximizing the overall operation of an establishment. Both of them are interrelated with each other for improving building performance. Alas, lack of a thorough review of design and specification has thus created so many faults and defects during the conception and construction stages in which resulted later in high upkeep costs. For overcoming that issue, this paper will explore the potential of VM approach during the conception phase of bringing on a perfect (fewer defects) design specification of a building. The standard procedure of VM methodology practice which has involved a multidisciplinary project stakeholders in order to avoid the issue over design and unnecessary maintenance costs will be concluded as well.